2016
DOI: 10.5301/hipint.5000449
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Merits and Challenges Associated with Simultaneous Bilateral THA using the Direct Anterior Approach

Abstract: While simultaneous DAA THA presents challenges, our results suggest that simultaneous DAA THA may add value to the healthcare system without resulting in increased complications compared to sequential hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Concomitant to our results, several studies have exhibited no difference in LLD between simBTHA and stgBTHA [ 36 , 37 , 40 ]. However, LLD can yield patient dissatisfaction after THA [ 82 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concomitant to our results, several studies have exhibited no difference in LLD between simBTHA and stgBTHA [ 36 , 37 , 40 ]. However, LLD can yield patient dissatisfaction after THA [ 82 ].…”
Section: Discussionsupporting
confidence: 88%
“…Functional recovery was faster in simBTHA, as walking without support started earlier [ 36 ] and walking capacity was better postoperatively [ 21 , 28 ]. Rates of home-discharged patients for stgBTHA were higher in all studies [ 25 , 26 , 40 , 41 , 43 , 49 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The application of the DAA in one-stage bilateral THA was rarely reported. Brown et al [ 15 ] suggested that the DAA could be safely and effectively applied in one-stage bilateral THA without resulting in increased complications compared to sequential hip arthroplasty if perioperative pain and blood loss could be properly managed. In a retrospective review covering 325 consecutive cases, Tamaki et al [ 16 ] concluded that, due to supine position and the minimally invasive nature of the DAA, the rate of systemic complications such as dislocation was lower with one-stage bilateral THA.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of evidence were determined with the Oxford Centre for Evidence-based Medicine Levels of Evidence tool (2011) ( 26 ). A consensus was reached between both authors through discussion.…”
Section: Methodsmentioning
confidence: 99%